2019
DOI: 10.1177/1460458219894494
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter validation of a machine-learning algorithm for 48-h all-cause mortality prediction

Abstract: In order to evaluate mortality predictions based on boosted trees, this retrospective study uses electronic medical record data from three academic health centers for inpatients 18 years or older with at least one observation of each vital sign. Predictions were made 12, 24, and 48 hours before death. Models fit to training data from each institution were evaluated using hold-out test data from the same institution, and from the other institutions. Gradient-boosted trees (GBT) were compared to regularized logi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…We found that the ML algorithm predicted the need for mechanical ventilation within 24 h among COVID-19 patients with high sensitivity and specificity. This work builds upon our prior work developing algorithms to predict patient outcomes including sepsis [ 15 ], acute kidney injury [ 16 ], mortality [ 17 ], and patient stability and decompensation [ 18 ]. While machine learning algorithms have been applied to retrospective COVID-19 patient data, no equivalent algorithms have yet been validated in a prospective setting, despite urgent need.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the ML algorithm predicted the need for mechanical ventilation within 24 h among COVID-19 patients with high sensitivity and specificity. This work builds upon our prior work developing algorithms to predict patient outcomes including sepsis [ 15 ], acute kidney injury [ 16 ], mortality [ 17 ], and patient stability and decompensation [ 18 ]. While machine learning algorithms have been applied to retrospective COVID-19 patient data, no equivalent algorithms have yet been validated in a prospective setting, despite urgent need.…”
Section: Discussionmentioning
confidence: 99%
“…This study builds upon existing evidence about the ability of algorithms to successfully provide clinical decision support [ [15] , [16] , [17] , [18] ]. However, there are several limitations to this study.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality prediction tools aid in triage and resource allocation by providing advance warning of patient deterioration. Our prior work has validated machine-learning (ML) algorithms for their ability to predict mortality and patient stability in a variety of settings and on diverse patient populations [ [20] , [21] , [22] , [23] , [24] ].…”
Section: Introductionmentioning
confidence: 99%
“…In 17 studies, the authors reported their model as more useful or superior to the EWS. [20][21][22][23][26][27][28]34,[36][37][38][39][40][41] Four studies reported real-time detection of deterioration before regular EWS, 20,26,42 and three studies reported positive effects on patient-related outcomes. 26,35 Four negative effects were noted on the controllability, validity, and potential limitations.…”
Section: Effects Facilitators and Barriersmentioning
confidence: 99%